Quality Of Health Among Methadone Maintenance Treatment (MMT) Program Clients In Myanmar - Sun, Tun (2020)
HIV prevalence rate among PWIDs (People who inject drugs) in Myanmar is high at 28.5% based on 2014 IBBS results. More than 13,441 (16% of the estimated 83,000 PWIDs) have been on methadone treatment in 2017. Evaluation of the methadone program is vital for efficient service delivery. This study aimed to understand the context and important treatment factors of methadone maintenance treatment (MMT) program among clients in Myanmar. A total of 210 respondents were recruited through stratified random sampling from five cities in Myanmar where MMT program existed. Several study instruments such as WHO-QOL-BREF questionnaire, Verona Service Satisfaction Scale questionnaire for Methadone Treatment (VSSS-MT) and Addiction Severity Index (ASI) were used. The urine drug test was also conducted to confirm respondents’ drug use status. Study results showed that 45% (n=93) never injected heroin in the last 30 days, while 55.5% (n=116) injected heroin. The average daily methadone dose in this study was 83mg. Thirty-seven percent (n=74/200) had HIV, 16.27% (n=34/209) reported co-infection (HIV/HCV). More than one-third (36.5%, n=76) received high methadone dose (above 80mg), while 63.46% (n=132) received low dose. Higher methadone dose was associated with decreased in heroin use (p=0.034). In reviewing the quality of life (QOL) of the respondents, the total average score of respondents (QOL) was 60.8%; specifically, 60.1% in the physical domain, 63.1% in the psychological domain, 59.9% in the social relation domain, and 60.4% in the environmental domain. Low QOL scores were associated with low methadone service satisfaction.